Penerapan Inovasi Booklet Berbasis Proactive Learning dan Manajemen Mom and Kids - Miftahul Khairoh; Shinta Nur Rochmayanti; Rakhmalia Imeldawati; Ainun Ganisia (Rena Cipta Mandiri, 2025)
Maternal and neonatal morbidity remains a critical challenge in Indonesia, particularly within the Pasean Community Health Center area in Pamekasan. Key contributing factors include limited community-based education, poor knowledge of nutrition and pregnancy danger signs, and suboptimal health cadre capacity. This community service initiative aims to enhance knowledge, empower cadres through proactive education, and reduce morbidity via early detection. The intervention involves the PELEM MANIS (Proactive Learning and Management for Mom and Kids) booklet. Activities were conducted using a hybrid model (online and face-to-face) encompassing lectures, discussions, and demonstrations. Program effectiveness was evaluated through pre- and post-tests to measure knowledge, while awareness was assessed via K6 maternal coverage. Results demonstrated a significant increase in knowledge and awareness among pregnant women, parents, and health cadres regarding pregnancy, childbirth, and neonatal care. This improvement is evidenced by higher post-test scores. The innovative booklet proved effective and relevant in helping stakeholders identify and manage emergencies throughout the maternal and neonatal periods.